Bicycle use in the university community: Empirical analysis using MobiCampus-UdL data (Lyon, France) - Havet, Nathalie; Bouzouina, Louafi (Journal of Transport and Land Use, 2024)
Promoting sustainable mobility systems by encouraging the use of the bicycle as a transport mode is now a public policy objective. This political will is also pursued in France where the modal share of cycling is relatively low. However, young people and those with a high level of human capital, such as members of the university community, are observed to be more advanced in their adoption of cycling. An understanding of how cycling is used by university students and staff would therefore help to inform public decision-making and support more efficient targeted policies to develop this mode of transport. Using original data from the MobiCampus-UdL project, the aim of this article is to analyze the determinants of bicycle use by the university community at the University of Lyon, France. Two multivariate logistic regression models are estimated on the subsamples of students and staff: one explaining the probability of using the bicycle as an exclusive mode of transport to get to the campus and the other explaining the probability of using the bicycle in combination with other modes. Our results suggest that while socio-demographic characteristics have little influence within our two relatively homogeneous subsamples, access to mobility resources and the spatial characteristics of the campus and place of residence are crucial. We also find that access to bicycles is an important determinant of the utilization of cycling. Given that the adoption of cycling is still very low, our findings justify policies to increase the availability of bicycles and subsidize their purchase. More specifically, our results suggest that access to a shared bike station on campus encourages the exclusive use of bicycles by students and staff but has no effect when used in combination with other modes. On the other hand, good accessibility to public transport, whether from home or from campus, does not reduce the use of bicycles by either sub-population, either exclusively or in combination. Furthermore, while living far from the city center is an obstacle to the exclusive use of the bicycles, especially for staff, it does not in any way prevent their use in combination with other modes, such as the train. These results open up new avenues for anticipating the development of intermodality between public transport and cycling.